Important Things to Know about Medicare: Chapter Ten--Key Terms, Additional Resources, List of Handouts, and References - Amanda Terminello; Martie Gillen (EDIS)
Important Things to Know about Medicare is a series of 10 publications that will cover the most common Medicare concerns. The series will provide general information about Medicare, including the four major plans, supplemental policies, interactions with different types of insurance, and assistance programs.